The Effects Of Self-Esteem on Academic Motivation: The Mediating Role of Automatic Thoughts - Cemaliye DIREKTOR (Muhammed Yıldız, 2017)
The purpose of the present study is to investigate the mediational role of automatic thoughts on the association between self-esteem and academic motivation. Differences would be analyzed separated according to gender and faculty studied. Participants of the study are 210 undergraduate students (%42.4, 89 women; %57.6, 121 men) selected randomly from counselling and intelligence teaching departments of University in Northern Cyprus. All permissions were taken. In order of the aim of self-esteem were assessed using ‘Rosenberg Self-Esteem Questionarie’’. In addition academic motivation was measured by ‘Academic Motivation Scale’ and ‘Automatic Thoughts Inventory’was used in measuring automatic thought levels of the participants. At this study relational screening analysis used, and mediation effect of automatic thoughts were analyzed using Baron and Kenny’s (1986) mediation analysis method. Partial mediation effect of amotivation subscale was proved among self-esteem and negative automatic thought. Evaluating the total effect and direct effect, it is indicated that, the difference is 28% of indirect effect value. Amotivation is related to self esteem and negative automatic thoughts